South American Fruit Fly (suggested common name) Anastrepha fraterculus (Wiedemann) (Insecta: Diptera: Tephritidae) - Vanessa Simões Dias; Andrea Lucky (EDIS)
This fact sheet supercedes EENY-266/IN545 (originally published as DPI Entomology Circular 217),  by H. H. Weems. Jr.